The Relationship between Burnout Syndrome and Nurse Organizational Commitment at Hospital - Retno Purwandari; Alfid Tri Afandi; Dyah Ayu Riski Imani (NurseLine Journal, 2022)
Burnout syndrome relates to mental fatigue, loss of commitment, and motivation to decline sequentially. One of the ways that can be done to increase organizational commitment to nurses is to reduce the workload, which can cause work burnout problems for nurses. If burnout can be reduced, organizational commitment to nurses will increase. To analyze how the relationship between burnout syndrome and the organizational commitment of nurses in the inpatient hospital. This research method is non-experimental, which uses a correlational research design to explain the correlative relationship between variables. The population of this study was all nurses in the inpatient room of the Tk. III Baladhika Husada Jember and all the nurses in the inpatient room of Bhayangkara Bondowoso Hospital with 117 nurses. The sampling technique used by researchers in this study was total sampling. The data collection technique used was a questionnaire. The achievement of burnout syndrome nurses in inpatient hospitals (29% of the total score of 217). Achievement of nurses' organizational commitment in the inpatient hospital (66% of the total score of 104). This study concludes that it has a strong relationship with the direction of the negative relationship between burnout and organizational commitment to nurses in the hospital inpatient room. Therefore, to increase the organizational commitment of nurses, it must minimize burnout syndrome.